Variant Human Immunodeficiency Virus Type 1 Proteases and Response to Combination Therapy Including a Protease Inhibitor - Servais, Jean (American Society for Microbiology, 2001)
The objective of this observational study was to assess the genetic variability in the human immunodeficiency virus (HIV) protease gene from HIV type 1 (HIV-1)-positive (clade B), protease inhibitor-naïve patients and to evaluate its association with the subsequent effectiveness of a protease inhibitor-containing triple-drug regimen. The protease gene was sequenced from plasma-derived virus from 116 protease inhibitor-naïve patients. The virological response to a triple-drug regimen containing indinavir, ritonavir, or saquinavir was evaluated every 3 months for as long as 2 years (n = 40). A total of 36 different amino acid substitutions compared to the reference sequence (HIV-1 HXB2) were detected. No substitutions at the active site similar to the primary resistance mutations were found. The most frequent substitutions (prevalence, >10%) at baseline were located at codons 15, 13, 12, 62, 36, 64, 41, 35, 3, 93, 77, 63, and 37 (in ascending order of frequency). The mean number of polymorphisms was 4.2. A relatively poorer response to therapy was associated with a high number of baseline polymorphisms and, to a lesser extent, with the presence of I93L at baseline in comparison with the wild-type virus. A71V/T was slightly associated with a poorer response to first-line ritonavir-based therapy. In summary, within clade B viruses, protease gene natural polymorphisms are common. There is evidence suggesting that treatment response is associated with this genetic background, but most of the specific contributors could not be firmly identified. I93L, occurring in about 30% of untreated patients, may play a role, as A71V/T possibly does in ritonavir-treated patients.